2013
DOI: 10.1007/978-3-642-39215-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Migration Tolerant Human Computer Interaction for Air Traffic Controllers

Abstract: Human machine interfaces (HMI) in the product division of air traffic management (ATM) are in use for long time spans. For an efficient use of HMIs not only user centered but also migration tolerant designs are important. Migration tolerance therefore means considering future requirements for a long lasting controller HMI life cycle. For efficient ATM, the concept of system wide information management (SWIM) will be introduced. This generates a large amount of additional information that will influence control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Keeping the goal of a commercial use in mind, this article presents a concept to enable the integration of a certain number of RPAS movements at the same time. Furthermore, experience has shown that changing rules and operating principles of aviation is a difficult, slow and lengthy process, which leads to the requirement that the introduction of new systems like RPAS or autonomous UAS must follow the principles of "migration tolerance" [7].…”
mentioning
confidence: 99%
“…Keeping the goal of a commercial use in mind, this article presents a concept to enable the integration of a certain number of RPAS movements at the same time. Furthermore, experience has shown that changing rules and operating principles of aviation is a difficult, slow and lengthy process, which leads to the requirement that the introduction of new systems like RPAS or autonomous UAS must follow the principles of "migration tolerance" [7].…”
mentioning
confidence: 99%